Food Quality, Price Fairness And Physical Environment On Customer Satisfaction In Korean Restaurants In Jakarta - Chelsea Laurent Kurniawan; Frenick Halim; Broto Mudjianto; Juliana juliana; Rosianna Sianipar; Arifin Djakasaputra (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The growth of the Korean restaurant industry in Jakarta has attracted significant attention, but little research has investigated the factors affecting customer satisfaction in this neighborhood. The aim of this study was to find out the impact of food quality, physical environment, and price fairness on customer satisfaction at a Korean restaurant in Jakarta. The research was carried out due to the low number of people visiting Korean restaurants and low consumer satisfaction. The research was carried out using quantitative methods with an approach to testing causal hypotheses. The respondents were 113 consumers of Korean restaurants in Jakarta. The analytical tool used is SPSS. The research finds the importance of food quality, fair price, and physical environment in creating customer satisfaction at a Korean restaurant in Jakarta. Governments can provide regulations on service standards and standards of restaurant management as well as provide education to restaurant entrepreneurs so that restaurant managers have adequate quality standards. Restaurant management needs to pay attention to these aspects to improve customer experience and maintain customer loyalty in an increasingly competitive market.